PENGARUH VARIASI JUMLAH ISOLAT BAKTERI PADA PUPUK ORGANIK KULIT KOPI (POKP) TERHADAP PERTUMBUHAN TANAMAN CABAI KERITING ( Capsicum annum L) DENGAN PENANAMAN SISTEM TUMPANGSARI UNTUK PENYUSUNAN BROSUR SOSIALISASI KEPADA MASYARAKAT - Suprayitno, Suprayitno; Muhfahroyin, Muhfahroyin; Sutanto, *Agus (Universitas Muhammadiyah Metro, 2023)
Chili is one of the important vegetable commodities that have prospective business opportunities. Curly chili pepper is one of the important horticultural plants that are cultivated commercially. Organik fertilizers include the compound fertilizers because they contain macronutrients (N, P, K) and micronutrients (Ca, Mg, Fe, Mn, Bo, Zn, and Co) which can improve the structure of soil fertility. This study aimed to find the effects of the application of coffee husk organik fertilizer (CHOF) for the growth of curly chili pepper (Capsicum annum L). The results showed that the organik fertilizer of coffee husk P3 variation with a total of 9 bacterial isolates (50% composition of coffee husk, 25% leaves, 12.5% husk charcoal, and 12.5% goat manure) gave the best effect on growth (height and some shoots) on curly chili pepper plants (Capsicum annum L). The results of Brochure validation showed that brochures were possible to use as the information media in the world of formal and non-formal education.